What Is Equus? Reconciling Taxonomy and Phylogenetic Analyses - Barrón-Ortiz, Christina I.; Avilla, Leonardo S.; Jass, Christopher N.; Bravo-Cuevas, Víctor M.; Machado, Helena; Mothé, Dimila (Frontiers in Ecology and Evolution, 2019)
Interest in the origin and evolution of Equus dates back to over a century, but there is still no consensus on the definition of the genus or its phylogenetic position. We review the placement of Equus within several phylogenetic frameworks and present a phylogenetic analysis of derived Equini, including taxa referred to Equus, Haringtonhippus, Dinohippus, Astrohippus, Hippidion, and Boreohippidion. A new, morphology-based phylogenetic tree was used as an initial hypothesis for discussing what taxa Equus encompasses, using four criteria previously used to define the genus category in mammals: phylogenetic gaps, uniqueness of adaptive zone, crown group definition, and divergence time. According to the phylogenetic gaps criterion, Equus encompasses clade 6 (Ha. francisci = E. francisci, E. conversidens, E. quagga, E. hemionus, E. mexicanus, E. ferus, E. occidentalis, and E. neogeus) based on morphological synapomorphies. Equus is assigned to clade 6, or possibly clade 7, according to the uniqueness of adaptive zone criterion. The crown group criterion places Equus at clade 6. Based on the time-calibrated phylogeny of Equini, the divergence time criterion suggests that Equus encompasses clade 9. This clade comprises all taxa traditionally assigned to Equus analyzed in our study, including the eight taxa listed above as well as E. stenonis, E. idahoensis, and E. simplicidens; the latter two are sometimes referred to the subgenus Plesippus and the former to the subgenus Allohippus. With the exception of the divergence time criterion, the results of our evaluation are congruent in identifying clade 6 as the most suitable position for Equus. The taxonomic implications of delimiting Equus to clade 6 in our phylogenetic tree include elevation of Allohippus and Plesippus to generic rank, assignment of a new genus to “Dinohippus” mexicanus, and synonymy of Haringtonhippus with Equus.